Multicrop germplasm collection from central Meghalaya, India, and the diversity range - Pal, A.K.=700 1 Barua, U.; Srivastava, R.; Hore, D.K.
(En, Fr, Es)
ilus., 9 ref.
Keywords: GERMOPLASMA; COLECCION DE MATERIAL GENETICO; VARIACION GENETICA; ARROZ; MAIZ; CAUPI; CITRUS; ITALIA